Distal femoral extension and shortening osteotomy as a part of multilevel surgery in children with cerebral palsy - Klotz, Matthias C. M.; Hirsch, Klemens; Heitzmann, Daniel; Maier, Michael Wolfgang; Hagmann, Sébastien; Dreher, Thomas (World journal of pediatrics, 2017)
BackgroundThere are several reports describing an increase in anterior pelvic tilt after hamstring lengthening in children with cerebral palsy (CP). Distal femoral extension and shortening osteotomy (DFESO) is an alternative treatment for correction of flexed knee gait, but investigations analyzing outcome and influence on adjacent joint are few in the literature. The purpose of this study was to analyze the influence of DFESO on knee and pelvis in children with CP. Furthermore, it was of interest if an additional patellar tendon advancement (PA) influences outcome.MethodsIn this retrospective study, 31 limbs of 22 children (GMFCS I-III; mean age: 12.1±3.1 years), who received DFESO were included and kinematic parameters (knee, pelvis) measured by 3-D-gait analysis were compared before and at least 1 year after surgery (mean follow-up period: 15.6 months).ResultsAfter surgery, during stance phase minimum knee flexion improved significantly by 20.5° (P<0.001) and mean anterior pelvic tilt increased by 4.0 degrees (P=0.045). In 16 limbs, the postoperative increase in maximum anterior pelvic tilt was more than 5°. Limbs who received an additional PA showed the biggest increase in anterior pelvic tilt.ConclusionsDFESO is an effective method for correction of flexed knee gait in children with CP. Furthermore, the results of this study indicate that DFESO may lead to an increase in anterior pelvic tilt, which may lead to a recurrence of flexed knee gait. In this context, PA seemed to aggravate the effect on the pelvis.
Online First December 2016
Gesehen am 25.09.2018